Earthquakes and Their Impact on Buildings and Structures - Qurbonov Jakhongir Komiljon Ogli (Genius Journals, 2022)
The article analyzes earthquakes and their impact on buildings and structures.
Keywords: Earthquakes; earthquake resistance; seismic forces